Liposome-Tethered Gold Nanoparticles Triggered by Pulsed NIR Light for Rapid Liposome Contents Release and Endosome Escape - Anisha Veeren; Maria O. Ogunyankin; Jeong Eun Shin; Joseph A. Zasadzinski (MDPI AG, 2022)
Remote triggering of contents release with micron spatial and sub-second temporal resolution has been a long-time goal of medical and technical applications of liposomes. Liposomes can sequester a variety of bioactive water-soluble ions, ligands and enzymes, and oligonucleotides. The bilayer that separates the liposome interior from the exterior solution provides a physical barrier to contents release and degradation. Tethering plasmon-resonant, hollow gold nanoshells to the liposomes, or growing gold nanoparticles directly on the liposome exterior, allows liposome contents to be released by nanosecond or shorter pulses of near-infrared light (NIR). Gold nanoshells or nanoparticles strongly adsorb NIR light; cells, tissues, and physiological media are transparent to NIR, allowing penetration depths of millimeters to centimeters. Nano to picosecond pulses of NIR light rapidly heat the gold nanoshells, inducing the formation of vapor nanobubbles, similar to cavitation bubbles. The collapse of the nanobubbles generates mechanical forces that rupture bilayer membranes to rapidly release liposome contents at the preferred location and time. Here, we review the syntheses, characterization, and applications of liposomes coupled to plasmon-resonant gold nanostructures for delivering a variety of biologically important contents in vitro and in vivo with sub-micron spatial control and sub-second temporal control.